Changing classes : - Packer, Martin J. (Cambridge University Press, 2001)
How do schools help to create the kind of person a child becomes? Changing Classes tells the story of a small, poor, ethnically-mixed school district in Michigan's rust-belt, a community in turmoil over the announced closing of a nearby auto assembly plant. As teachers and administrators found ways to make schooling more relevant to working-class children, two large-scale school reform initiatives swept into town: the Governor's 'market-place' reforms and the National Science Foundation's 'state systemic initiative'. All this is set against the backdrop of the transformation to a global, post-Fordist economy. The result is an account of the complex linkages at work as society structures the development of children to adulthood.